The value of movement content knowledge in the training of Australian PE teachers: perceptions of teacher educators. Issue 2 (4th May 2019) - Backman, Erik; Pearson, Phil; Forrest, Gregory John
ABSTRACT: The purpose of this paper is to describe, analyse and discuss the statements made by Australian physical education teacher educators (PETE) in terms of how they perceive and value movement content knowledge (CK) in their assessment of movement courses. Drawing on Shulman's perspective of CK, this paper builds on qualitative analysis of in-depth interviews with nine teacher educators from a total of seven PETE universities in New South Wales as well as written unit outlines including assignments from these PETE universities. The main results from the study show that among the participants, movement CK is conceptualised as physical movement performance. This conceptualisation limits the value placed on movement CK in the assessment of PETE students. Further, movement courses are often assessed using written assignments rather than practice-oriented assignments. The findings have been analysed and discussed in relation to Shulman-inspired concepts of CK and pedagogical content knowledge (PCK), as well as in relation to epistemological perspectives in PETE.